Suppression of fusarium wilt in banana and growth promotion by the beneficial fungus trichoderma asperellum TRC900 is cultivar-dependent - Sarma, M.; Zorrilla-Fontanesi, Y.; Uma, S.; Vanderschuren, H.; Swennen, R.; De Coninck, B. (Elsevier, 2025)
The hemibiotrophic, soil-borne fungal pathogen Fusarium oxysporum f.sp. cubense TR4 (Foc TR4) poses a major threat to global banana production, with no effective management method currently available. Therefore, the identification of eco-friendly strategies to mitigate Fusarium wilt of banana (FWB) is crucial. Biological control organisms (BCOs), like Trichoderma spp., can directly suppress pathogen growth and enhance plant defense responses, thereby improving crop yields. Two commercial Trichoderma asperellum strains, TRC900 and T34, were tested for their efficacy in reducing FWB symptoms in two Cavendish banana cultivars (cvs.), ‘Valery’ and ‘Grand Naine’. In vitro bioassays showed both strains inhibited Foc TR4 mycelial growth by 40%. Inoculation of ‘Valery’ with TRC900 significantly reduced FWB symptoms when applied in the same pot as Foc TR4, while T34 did not. In ‘Valery’, TRC900 also reduced symptoms in a split-root setup, suggesting that TRC900 triggers induced resistance (IR). In ‘Grand Naine’, neither strain reduced disease symptoms. Both strains were also assessed for their ability to promote banana plant growth in absence of Foc TR4. In ‘Valery’, both strains significantly increased plant growth, while in ‘Grand Naine’, TRC900 reduced growth and T34 had minimal effect. Plant defense responses and growth promotion by T. asperellum were influenced by both the banana cultivar and the Trichoderma strain. Root colonization bioassays indicated TRC900 was more efficient in colonizing ‘Valery’ roots, suggesting that biocontrol effect could be attributed to enhanced colonization. These findings highlight how a single BCO can elicit different responses in closely-related cvs., influencing the outcome of plant-BCO-pathogen interactions.